Adenosine receptor inhibition attenuates the suppression of postexercise cutaneous blood flow. (30th April 2014) - McGinn, Ryan; Fujii, Naoto; Swift, Brendan; Lamarche, Dallon T.; Kenny, Glen P.
Abstract : Key points: Skin blood flow (SkBF) is an important avenue for heat loss; however, it is rapidly suppressed after exercise despite persistently high core and muscle temperatures. This has been ascribed to altered active vasodilation; however, recent work has identified a role for adenosine receptors in the decrease in SkBF following passive heating. In this study, we examined whether adenosine receptors are involved in the postexercise regulation of SkBF by infusion of 4 mm theophylline (a non‐selective adenosine receptor antagonist) via microdialysis. We show that adenosine receptors have a major role in modulating postexercise SkBF, as evidenced by a marked elevation during theophylline infusion compared to a control site. These results help us to better understand the mechanisms underlying the postexercise reduction in SkBF and subsequently heat loss which is associated with heat‐related illness and/or injury. Abstract: The time‐dependent contributions of active vasodilation (e.g. nitric oxide) and noradrenergic vasoconstriction to the postexercise suppression of cutaneous perfusion despite persistent hyperthermia remain unknown. Moreover, adenosine receptors have been shown to mediate the decrease in cutaneous perfusion following passive heating. We examined the time‐dependent modulation of nitric oxide synthase, noradrenergic vasoconstriction and adenosine receptors on postexercise cutaneous perfusion. Eight males performed 15 min of high‐intensity (85% V O 2 max ) cycling followed by 60 min of recovery in temperate ambient conditions (25°C). Four microdialysis probes were inserted into the forearm skin and continuously infused with: (1) lactated Ringer solution (Control); (2) 10 mm N G ‐nitro‐l ‐arginine methyl ester (l ‐NAME; nitric oxide synthase inhibitor); (3) 10 mm bretylium tosylate (BT; inhibitor of noradrenergic vasoconstriction); or (4) 4 mm theophylline (THEO; adenosine receptor inhibitor). Cutaneous vascular conductance (CVC) was expressed as a percentage of maximum and was calculated as perfusion units (laser Doppler) divided by mean arterial pressure. End‐exercise CVC was similar in Control, THEO and BT ( P > 0.1), but CVC withl ‐NAME (39 ± 4%) was lower than Control (59 ± 4%, P < 0.01). At 20 min of recovery, Control CVC (22 ± 3%) returned to baseline levels (19 ± 2%, P = 0.11). Relative to Control, CVC was reduced byl ‐NAME for the first 10 min of recovery whereas CVC was increased with BT for the first 30 min of recovery ( P < 0.03). In contrast, CVC with THEO was elevated throughout the 60 min recovery period ( P ≤ 0.01) compared to Control. We show that adenosine receptors appear to have a major role in postexercise cutaneous perfusion whereas nitric oxide synthase and noradrenergic vasoconstriction are involved only earlier during recovery.